Experimental investigation of parametric sloshing in a tank with vertical baffles. (1st October 2020) - Yu, Liting; Xue, Mi-An; Jiang, Zhouyu
Abstract: Free surface of parametric sloshing will undergo unbounded motion, resulting in destabilization, if the combination of excitation frequency and amplitude is located in instable regions. In studies of parametric sloshing, high modes are of great concern. Our experimental results showed that dimensionless free surface elevations of parametric sloshing in a clean tank induced by high-frequency excitation were much larger than that induced by low-frequency excitation. The effectiveness of baffles in suppressing parametric sloshing and the damping mechanism of baffles were investigated and analyzed. Results showed that vertical baffles performed well in suppressing parametric sloshing. The optimal number and position of baffles to suppress sloshing depended on sloshing modes. Two noteworthy findings were revealed. One was the complete failure of one baffle in suppressing parametric sloshing of the second mode, and the other was that two baffles were less effective than one baffle in suppressing parametric sloshing of the first and the third modes. By changing the number and positions of baffles, it was concluded that the closer the position of the baffles to the nodes of sloshing modes, the more powerful the damping effect of baffles. The discovery of damping mechanism cogently explained the two noteworthy findings mentioned above. Highlights: Participation of higher sloshing modes in a rectangular tank vertically driven are accounted. Optimal number of baffles to suppress sloshing depends on the sloshing mode. Optimal position of baffles to suppress sloshing depends on the distance between baffles and the nodes of sloshing mode.